Characteristics of Alveolar Inter-Cortical Osteotomy Technique on the Maxilla (Global Journal of Medical Research, 2015)
Main statements of inter-cortical osteotomy technique of the alveolar crest with its horizontal atrophy are envisioned. Criteria for patient selection for the technique utilization are presented. Some aspect of prophylaxis against postoperative adverse effects and complications are discussed.
Keywords: alveolar crest splitting; vestibular advance-ment of the cortical plate; dental implant; osteoplastic material